The effects of using sense relations in learning English vocabulary of 9th grade students in a secondary school in Hanoi = Ảnh hưởng của việc sử dụng mối quan hệ về nghĩa vào việc học từ vựng của học sinh lớp 9 tại một trường THCS ở Hà Nội. M.A - Dương, Thị Hương (2019)
Vietnamese students often face difficulties in learning vocabulary. They fail to remember words and to recall words when necessary because of their learning habits and learning strategies. Based on literature review, it is found that sense relations can have positive effects on vocabulary learning. This thesis is entitled “The effects of using sense relations on learning English vocabulary of 9th grade students in a secondary school in Hanoi” which aims to find out the improvement of the use of sense relations in teaching vocabulary.